1993
DOI: 10.1080/00288330.1993.9516585
|View full text |Cite
|
Sign up to set email alerts
|

Redd characteristics and implications for survival of Chinook salmon (Oncorhynchus tshawytscha) embryos in the Waitaki River, New Zealand

Abstract: Chinook salmon (Oncorhynchus tshawytscha) redd characteristics were measured at three locations in the glacially-sourced mainstem and two locations in small, primarily rainfed, tributaries of the lower Waitaki River. Mean redd size was 17.5 m 2 ; lengths of redds ranged from 2.4 to 10 m and their widths ranged from 1.2 to 9.5 m. Water depth (mean ± SD = 0.37 ± 0.09 m) and water velocity (mean 0.68 ± 0.27 m s -1 ) were significantly different between two of the mainstem locations but this may have resulted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Many studies conclude that spawning salmonids select for depth beyond the simple access criterion described here and without considering mesohabitat-scale variation (e.g., Burner, 1951;Beland et al, 1982;Deverall et al, 1993). In the absence of sedimentary requirements, we propose that this apparent 'selection' within riffles is autocorrelative and an artefact of the implicit inverse-relationship between depth and velocity in channels as dictated by open channel flow mechanics.…”
Section: Discussionmentioning
confidence: 69%
“…Many studies conclude that spawning salmonids select for depth beyond the simple access criterion described here and without considering mesohabitat-scale variation (e.g., Burner, 1951;Beland et al, 1982;Deverall et al, 1993). In the absence of sedimentary requirements, we propose that this apparent 'selection' within riffles is autocorrelative and an artefact of the implicit inverse-relationship between depth and velocity in channels as dictated by open channel flow mechanics.…”
Section: Discussionmentioning
confidence: 69%
“…We developed a set of 32 flow simulations using paired mean flow depth and velocity values obtained at redd locations along the Sacramento River for Chinook salmon (Oncorhynchus tshawytscha) (Table 4) (Data from NOAA, Andrew Pike, Winter-run Chinook salmon Lifecycle model project, see data repository). The Sacramento River data (19 velocity-depth sets) were augmented with one set of surface water information from the Columbia River (Mueller, 2005), six sets of Fehlman's (1985) flume experimental runs, two sets from Deverall's (1993) field data, and four additional depth-velocity sets to increase the range to shallower flow conditions than those observed in the data of the Sacramento River. We used three redd sizes to account for their natural variation: large, medium, and small, with lengths of 3.9, 2.8, and 1.82 m and aspect ratios of 0.077, 0.139, and 0.265, respectively (Deverall et al, 1993;Evenson, 2001;Tonina & Buffington, 2009a).…”
Section: Flow Scenariosmentioning
confidence: 99%
“…Salmon females bury their eggs in streambed gravel, forming an egg nest (Crisp & Carling, 1989;Deverall et al, 1993) having a typical dune-like shape (Figure 1). These dune-like features are commonly referred to as a redd.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depending on where and how permeability was measured, discrepancies may appear between authors (Chapman, 1988). Deverall et al (1993) found permeabilities in some redds of New Zealand chinook salmon O. tshawytscha (Walbaum) as high as 9000 cm h 1 , and half were over 5500 cm h 1 . They suspected that developing embryos may be stressed by excessive interstitial water velocity due to the high substratum permeability.…”
Section: Etf Survival and Substratum Permeabilitymentioning
confidence: 99%
“…They suspected that developing embryos may be stressed by excessive interstitial water velocity due to the high substratum permeability. Brannon (1965, in Deverall et al, 1993 showed that for permeabilities >5500 cm h 1 , fewer sockeye salmon O. nerka (Walbaum) alevins survived to yolk absorption and that survivors were generally smaller than alevins incubated at lower permeabilities. In many redds studied on Gotland, permeability was >5500 cm h 1 without any observed decrease of the ETF survival (Table IV) Garside (1966) (1) In Chapman 1988, (2) in Heard 1991, (3) in Alderdice et al, 1958.…”
Section: Etf Survival and Substratum Permeabilitymentioning
confidence: 99%